Peningkatan manajemen usaha mikro kecil dan menenggah (UMKM) kursi bambu di Desa Laweyan - Ummi Latifah; Ahmad Alfan Abrori; Alfi Mirsa Salsabila; Moh. Umar Abdul Hadi (Jurnal Dedikasi Masyarakat, 2024)
Micro, Small, and Medium Enterprises (MSMEs) specializing in bamboo crafts hold significant potential to drive local economic growth. However, they often face several challenges, such as suboptimal business management, limited production tools, and inadequate utilization of digital technology in marketing. This community engagement program aims to enhance the capacity and competitiveness of bamboo chair MSMEs in Laweyan Village, Probolinggo Regency, through business management training and digital marketing strategies. The program was implemented in four stages: preparation, implementation, monitoring, and evaluation. The results indicate improved partner understanding of business management, strategic business planning, and the application of digital marketing through social media and online marketplaces. Furthermore, MSME partners have begun to apply time management in their production processes and expanded their market reach by establishing online stores. This training has proven effective in strengthening business capacity and promoting the sustainability of bamboo craft MSMEs amidst the dynamics of a modern market economy.